2010
DOI: 10.1007/s10753-010-9191-6
|View full text |Cite
|
Sign up to set email alerts
|

Zileuton Reduces Inflammatory Reaction and Brain Damage Following Permanent Cerebral Ischemia in Rats

Abstract: 5-Lipoxygenase inhibitor zileuton has been demonstrated to attenuate ischemic brain damage in rats of permanent focal cerebral ischemia in previous work. To further investigate the mechanism underlying zileuton's neuroprotection, adult male Sprague-Dawley rats underwent permanent middle cerebral artery occlusion (MCAO), then received treatment with zileuton or vehicle after the onset of ischemia. Neurological deficit, cerebral infarction, and morphological characteristic were measured 6 and 24 h after MCAO. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In agreement to this result Tu et al [61] demonstrated that enzymatic activity of MPO was increased at 6 h after pMCAO with a peak at 24 h, especially in the cortex. Wang et al [62] found that increased MPO activity persist longer in the cortex than in the striatum and can still be found in the cortex after 120 h. The treatment with Etyol significantly protected ischemic animals against the increase in MPO activity.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement to this result Tu et al [61] demonstrated that enzymatic activity of MPO was increased at 6 h after pMCAO with a peak at 24 h, especially in the cortex. Wang et al [62] found that increased MPO activity persist longer in the cortex than in the striatum and can still be found in the cortex after 120 h. The treatment with Etyol significantly protected ischemic animals against the increase in MPO activity.…”
Section: Discussionsupporting
confidence: 68%
“…Developing novel 5-LOX inhibitor or 5-LOX/COX-2 dual inhibitor is a therapeutic strategy to treat inflammatory diseases including arthritis [45]. Neuro-inflammation of brain damage induced by permanent cerebral ischemia and renal ischemia-reperfusion injury can be protected by treatment of zileuton, a 5-LOX inhibitor [46], [47]. 5-LOX inhibitor, NDGA is reported to attenuate ovalbumin-induced lung inflammation in rats [48].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that proinflammatory cytokines, including TNF-α and IL-1ÎČ are elevated in serum in the early phase of acute ischemic stroke [26,27].…”
Section: Discussionmentioning
confidence: 99%